Beyond Skills: Understanding Teachers’ Technology Integration Through Self-Determination Theory in Low-Resource Contexts - Friska Ria Sitorus; Riris Marito Tamba (LP. Ma'arif Janggan Magetan, 2026)
Despite the growing integration of technology in education, many elementary school teachers particularly those in suburban areas continue to demonstrate limited ICT proficiency. While previous studies have extensively examined technology integration and teacher motivation, there remains a lack of in-depth qualitative research exploring how senior teachers with limited digital competence experience and negotiate technology adoption through the lens of Self-Determination Theory (SDT), especially in under-resourced contexts. Addressing this gap, this study investigates senior elementary school teachers’ experiences in integrating technology into classroom practices, focusing on both the challenges encountered and the perceived benefits. Grounded in SDT, the study emphasizes the roles of autonomy, competence, and relatedness in shaping teachers’ motivation for technology use. A qualitative case study approach was employed, involving nine elementary school teachers from suburban areas in North Sumatra, Indonesia. The findings reveal that although teachers recognize the potential of technology to enhance teaching effectiveness and student engagement, they face significant barriers, including limited infrastructure, insufficient training, and difficulties aligning technology with pedagogy. The results further highlight that teachers’ motivation to adopt technology is strongly influenced by the fulfillment of their psychological needs. This study contributes to the literature by providing contextualized insights into how SDT operates in low-resource educational settings and underscores the importance of sustained professional development and systemic support to improve technology integration among teachers.